IMPROVING STUDENTS’ READING COMPREHENSION ACHIEVEMENT THROUGH QUESTION GENERATION STRATEGY - Meti Yulistia; Kiki Rizki Amelia (Universitas Islam Ogan Komering Ilir Kayuagung, 2020)
This study was aimed to find out whether or not there was a significant difference in reading comprehension achievement between students who were taught by using the Question Generation strategy and that of those who were not. In conducting the study, question generation strategy was used in the experimental group, but the control group did not get any treatment. Sixty students were assigned in two groups, with 30 students in the experimental group and the other 30 students in the control group. Reading comprehension tests was used in collecting the data. Data were analyzed using a t-test. The findings of the study showed that the question generation strategy could improve students’ reading achievement better than and those who were not. Therefore, the question generation strategy was helpful to aid students to understand the reading text